Splicing inhibition mediated by reduced splicing factors and helicases is associated with the cellular response of lung cancer cells to cisplatin - Lujuan Wang; Na Yin; Wenhua Shi; Yaohuan Xie; Junqi Yi; Ziying Tang; Jingqun Tang; Juanjuan Xiang (Computational and Structural Biotechnology Journal, 2024)
Lung cancer’s mortality is predominantly linked to post-chemotherapy recurrence, driven by the reactivation of dormant cancer cells. Despite the critical role of these reactivated cells in cancer recurrence and metastasis, the molecular mechanisms governing their therapeutic selection remain poorly understood. In this study, we conducted an integrative analysis by combining PacBio single molecule real-time (SMRT) sequencing with short reads Illumina RNA-seq. Our study revealed that cisplatin-induced dormant and reactivated cancer cells exhibited a noteworthy reduction in gene transcripts and alternative splicing events. Particularly, the differential alternative splicing events were found to be overlapping with the differentially expression genes and enriched in genes related to cell cycle and cell division. Utilizing ENCORI database and correlation analysis, we identified key splicing factors, including SRSF7, SRSF3, PRPF8, and HNRNPC, as well as RNA helicase such as EIF4A3, DDX39A, DDX11, and BRIP1, which were associated with the observed reduction in alternative splicing and subsequent decrease in gene expression. Our study demonstrated that lung cancer cells reduce gene transcripts through diminished alternative splicing events mediated by specific splicing factors and RNA helicase in response to the chemotherapeutic stress. These findings provide insights into the molecular mechanisms underlying the therapeutic selection and reactivation of dormant cancer cells. This discovery opens a potential avenue for the development of therapeutic strategies aimed at preventing cancer recurrence following chemotherapy.